2001
DOI: 10.1136/jcp.54.10.737
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow trephine biopsy

Abstract: Trephine biopsies of the bone marrow should be carried out, when clinically indicated, by trained individuals following a standard operating procedure. A bone marrow aspiration should be performed as part of the same procedure. For patient safety and convenience, biopsies are usually performed on the posterior iliac crest. The biopsy specimen should measure at least 1.6 cm and, if it does not, consideration should be given to repeating the procedure, possibly on the contralateral iliac crest. If bone marrow as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(159 citation statements)
references
References 26 publications
1
151
0
7
Order By: Relevance
“…Bone marrow biopsy and aspiration (BMBA) is a commonly performed procedure indicated in the diagnosing and treatment of blood disorders and solid tumors [1,2]. For adults, the infiltration of local anesthesia at the biopsy site has been used as the principal form of analgesia for BMBA [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow biopsy and aspiration (BMBA) is a commonly performed procedure indicated in the diagnosing and treatment of blood disorders and solid tumors [1,2]. For adults, the infiltration of local anesthesia at the biopsy site has been used as the principal form of analgesia for BMBA [3].…”
Section: Introductionmentioning
confidence: 99%
“…In case of suspected plasma cell myeloma BMB is strongly recommended. 19 However in a study of Charles et al, who compared 79 simultaneous marrow aspirates and trephine biopsies from multiple myeloma patients, suggested that particulate aspirates may be at least as sensitive as trephine biopsies for detecting myeloma. 20 Out of 102 cases of pancytopenia, 20% of BMA showed erythroid hyperplasia, however, after correlation with biopsy, it reduced to 16.6%.…”
Section: Figure 6: Acute Myeloblastic Leukemia Myeloblasts With Finementioning
confidence: 99%
“…1 Focal hyperplasia of erythroid or granulocytic cells at a similar stage of maturation may be observed in hot spot. 19,21 A correlation with BME, clinical parameters and other laboratory parameters are required to trace the cause of pancytopenia in these cases. A possible hypersplenism needs to be ruled out in addition to different haemolytic anemias in cases of marrow showing erythroid hyperplasia.…”
Section: Figure 6: Acute Myeloblastic Leukemia Myeloblasts With Finementioning
confidence: 99%
“…A Trephine Biopsy [4] easily carried out on the Posterior Superior Iliac Spine, with the patient lying in the lateral position and the hip& knees in flexion. Ilium just below the Anterior Superior Iliac Spine is an alternative site, with the patient Supine and the approach being perpendicular to the Ilium.…”
Section: Discussionmentioning
confidence: 99%